Winter wheat septoria blotch (Zymoseptoria tritici) (literature review) - О. S. Kononenko; N. V. Shishkin; T. G. Derova (Зерновое хозяйство России)
In the Southern Federal District, winter wheat is a main food crop. One of the most important factors that can destabilize gross grain yields and reduce grain crop productivity are parasitic organisms. One of the most common wheat diseases is septoria blotch (Zymoseptoria tritici). The purpose of the current study was to analyze the biological cycle of distribution, harmfulness, measures to combat septoria blotch on winter wheat. The paper has considered the importance of winter wheat septoria disease in various countries and in Russia. There was noted a leading position in distribution and harmfulness of the disease, and according to the results of study conducted by Russian and foreign researchers, it was found that this pathogen was inferior in importance only to wheat rust. There were presented three types of septoria blotch pathogens and there was established a dominant type in the Southern Federal District. Yield losses caused by septoria blotch can reach upto 30-40%, and the optimal temperature for its development and spread is from 5 to 20°C, with frequent precipitation. There have been given the technological methods under which the crop damage by pathogens increased. There have been presented the measures to combat septoria blotch and there has been described the most effective, economical and environmentally friendly method, namely the development of resistant varieties and their introduction into production. There has been considered qualitative and quantitative resistance of varieties. Currently there have been identified 21 major septoria blotch resistance genes. There has been considered longevity of stb-genes and the reasons for its loss. It has been established that the development of winter wheat varieties resistant to septoria blotch is a priority issue of breeding, since this control measure reduces yield losses and potential reserve of the pathogen in the agrocenosis.